Positive electrode active material particles, positive electrode, and lithium ion battery

By designing a layered structure with high internal magnesium concentration and low surface magnesium concentration in the positive electrode active material particles and introducing carbon nanotubes, the problems of increasing initial resistance and deterioration of capacity retention are solved, and better electrochemical performance is achieved .

CN119447215APending Publication Date: 2025-02-14TOYOTA JIDOSHA KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411041366.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-04
Filing Date
2024-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The initial resistance increase and capacity retention rate deterioration of the existing cathode active material particles is mainly due to the concentration gradient of the decrease of magnesium (Mg) concentration from the particle surface to the center, which causes lithium (Li) diffusion and electron conduction to be inhibited, which in turn causes the increase in resistance and Cracks form.

Method used

The positive electrode active material particles with a layered rock salt type crystal structure are used, including a lithium composite oxide containing magnesium, whose internal magnesium concentration is higher than that of the surface magnesium concentration, and carbon nanotubes are introduced into the particles to improve electron conduction.

Benefits of technology

By increasing the internal magnesium concentration, the increase in the initial resistance is reduced and the deterioration of capacity retention is suppressed. At the same time, the introduction of carbon nanotubes further improves electron conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447215A_ABST
    Figure CN119447215A_ABST
Patent Text Reader

Abstract

The invention relates to positive electrode active material particles, a positive electrode, and a lithium ion battery. A positive electrode active material particle in which the positive electrode active material particle has a layered rock salt type crystal structure, the positive electrode active material particle contains a magnesium-containing lithium composite oxide, and the magnesium concentration in the interior of the positive electrode active material particle is higher than the magnesium concentration in the surface portion of the positive electrode active material particle.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications

[0002] This non-provisional application is based on Japanese Patent Application No. 2023-127491 filed with the Japan Patent Office on August 4, 2023, the entire contents of which are hereby incorporated by reference. Technical Field

[0003] The present disclosure relates to positive electrode active material particles, positive electrodes, and lithium ion batteries. Background Art

[0004] Japanese Patent Laid-Open No. 2018-88383 discloses a positive electrode active material for a non-aqueous electrolyte secondary battery, wherein the positive electrode active material contains magnesium (Mg) and has a concentration gradient in which the Mg concentration decreases from the particle surface to the center. Summary of the invention

[0005] When the Mg concentration on the particle surface is high, it inhibits the diffusion of lithium (Li) and also inhibits electronic conduction, etc., thereby possibly increasing resistance, especially initial resistance. In addition, when Mg exists only on the particle surface, the extension / contraction degree of the c-axis length occurring between the outer and inner parts of the positive electrode active material with charge and discharge is different, which may cause cracks to form inside, potentially leading to deterioration of capacity retention.

[0006] One object of the present disclosure is to suppress an increase in initial resistance and to suppress deterioration in capacity retention ratio.

[0007] [1] A positive electrode active material particle, wherein

[0008] The positive electrode active material particles have a layered rock salt type crystal structure,

[0009] The positive electrode active material particles include a lithium composite oxide containing magnesium, and

[0010] The magnesium concentration inside the positive electrode active material particle is higher than the magnesium concentration on the surface of the positive electrode active material particle.

[0011] When the Mg concentration in the interior is higher than the Mg concentration in the surface portion, it is believed that the effects of suppression of Li diffusion, suppression of electron conduction, etc. may be small, and as a result, the increase in initial resistance can be suppressed. It is also believed that because Mg is included, the elongation of the c-axis length of the positive electrode active material particles that may occur during charge and discharge can be suppressed, thereby suppressing the formation of cracks in the interior, thereby suppressing the degradation of the capacity retention rate.

[0012] [2] The positive electrode active material particle according to [1], wherein

[0013] The magnesium concentration in the interior is 0.5 mol % to 8.0 mol %, and

[0014] The magnesium concentration in the surface portion is 5.0 mol % or less.

[0015] [3] The positive electrode active material particle according to [1] or [2], wherein the difference between the magnesium concentration in the inner portion and the magnesium concentration in the surface portion is 1.0 mol % or more.

[0016] [4] A positive electrode comprising the positive electrode active material particles according to any one of [1] to [3].

[0017] [5] The positive electrode according to [4], further comprising carbon nanotubes.

[0018] [6] A lithium ion battery comprising the positive electrode according to [4] or [5].

[0019] The foregoing and other objects, features, aspects and advantages of the present disclosure will become more apparent from the following detailed description of the present disclosure when read in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a cross-sectional view of a positive electrode active material particle according to the present embodiment.

[0021] Figure 2 is a conceptual diagram showing an example of a lithium ion battery according to the present embodiment.

[0022] Figure 3 : is a table showing the first battery configuration.

[0023] Figure 4 : is a table showing the second battery configuration.

[0024] Figure 5 : is a table showing the third battery configuration.

[0025] Figure 6 This is a table showing the configurations of samples and evaluation results in Examples and Comparative Examples. DETAILED DESCRIPTION

[0026] Next, an embodiment of the present disclosure (hereinafter also referred to as "the present embodiment") and an example of the present disclosure (hereinafter also referred to as "the present example") will be described. It should be noted that neither the present embodiment nor the example limit the technical scope of the present disclosure.

[0027] A stoichiometric composition formula represents a typical example of a compound. A compound can have a non-stoichiometric composition. For example, "Al 2 O 3" is not limited to compounds in which the ratio of the amount of substances (molar ratio) is "Al / O=2 / 3". Unless otherwise specified, "Al 2 O 3 " denotes a compound containing Al and O in any composition ratio. In addition, for example, the compound may be doped with a trace element, or a part of Al and / or O may be replaced by other elements.

[0028] "Derivative" refers to a compound derived from its original compound by at least one partial modification of the group consisting of functional group introduction, atom replacement, oxidation, reduction and other chemical reactions. The position of modification can be one position, or can be multiple positions. "Substituent" can include at least one of the group consisting of, for example, alkyl, alkenyl, alkynyl, cycloalkyl, unsaturated cycloalkyl, aryl, heterocyclic radical, halogen atoms (F, Cl, Br, I, etc.), OH, SH, CN, SCN, OCN, nitro, alkoxy, unsaturated alkoxy, amino, alkylamino, dialkylamino, aryloxy, acyl, alkoxycarbonyl, acyloxy, aryloxycarbonyl, acylamino, alkoxycarbonylamino, aryloxycarbonylamino, sulfonylamino, sulfamoyl, carbamoyl, alkylthio, arylthio, sulfonyl, sulfinyl, urea, phosphoramido, sulfo, carboxyl, hydroxamic acid, sulfinyl, hydrazine, imino, silyl, etc. These substituents can be further substituted. When there are two or more substituents, these substituents may be the same as each other, or may be different from each other. A plurality of substituents may be combined together to form a ring.

[0029] The "copolymer" includes at least one selected from the group consisting of an unspecified type, a statistical type, a random type, an alternating type, a periodic type, a block type, and a graft type.

[0030] <<Positive Electrode Active Material Particles>>

[0031] Figure 1 2 is a cross-sectional view of a positive electrode active material particle according to the present embodiment. The positive electrode active material particle 5 has a layered rock salt type crystal structure. The positive electrode active material particle 5 contains a lithium composite oxide containing Mg. The Mg concentration of the interior 1 of the positive electrode active material particle 5 is higher than the Mg concentration of the surface 2 of the positive electrode active material particle 5.

[0032] The positive electrode active material particles 5 have a layered rock salt type crystal structure. The crystal structure of the positive electrode active material particles 5 can be identified by, for example, inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0033] The positive electrode active material particles 5 contain a lithium composite oxide containing Mg. The composition of the lithium composite oxide containing Mg is not limited as long as the positive electrode active material particles 5 have a layered rock salt type crystal structure.

[0034] The Mg concentration (mol %) of the interior 1 of the positive electrode active material particle 5 is higher than the Mg concentration (mol %) of the surface portion 2 of the positive electrode active material particle 5. In other words, the composition of the interior 1 of the positive electrode active material particle 5 is different from the composition of the surface portion 2. When the Mg concentration of the interior 1 of the positive electrode active material particle 5 increases, it is expected that the effects of the suppression of Li diffusion, the suppression of electron conduction, etc. may become smaller, and as a result, the increase in initial resistance can be suppressed. It is also expected that the elongation of the c-axis length that may occur in the positive electrode active material particle 5 with charge and discharge can be suppressed, so that the formation of cracks in the interior 1 can be suppressed, thereby suppressing the degradation of the capacity retention rate. The Mg concentration of the interior 1 of the positive electrode active material particle 5 is not particularly limited as long as it is higher than the Mg of the surface portion 2 of the positive electrode active material particle 5. For example, the Mg concentration of the surface portion 2 of the positive electrode active material particle 5 can be 0 mol%. In addition, the Mg concentration of the positive electrode active material particle 5 can be, for example, continuously increased from the surface portion 2 of the positive electrode active material particle 5 to the interior 1.

[0035] In this embodiment, the "interior of the positive electrode active material particle" refers to the area at the center of gravity of the positive electrode active material particle and its vicinity, and generally refers to the area 100 nm or more inward from the outermost surface of the positive electrode active material particle toward the center of gravity. For example, when the positive electrode active material particle is a roughly spherical particle, the minimum circumscribed circle of the particle is drawn, and the area within 100 nm from the center of gravity can be regarded as the interior of the positive electrode active material particle. The "surface portion of the positive electrode active material particle" refers to the area from the surface of the positive electrode active material particle to 50 nm inward.

[0036] For example, the composition of the interior 1 of the Mg-containing lithium composite oxide is represented by the following formula (1).

[0037] Li a Ni (1-b) Mg b O c (1)

[0038] In the above formula (1), a satisfies the relationship of 1.00≤a≤1.20, b satisfies the relationship of 0.005≤b≤0.08, and c satisfies the relationship of 2.0≤c<2.1. b is preferably 0.01≤b≤0.06, and it may be 0.02≤b≤0.05.

[0039] For example, the composition of the surface portion 2 of the Mg-containing lithium composite oxide is represented by the following formula (2).

[0040] Li x Ni (1-y) Mg y O z (2)

[0041] In the above formula (2), x satisfies the relationship of 1.00≤x≤1.20, y satisfies the relationship of 0.00≤y≤0.05, and z satisfies the relationship of 2.0≤z<2.1. For example, y may be 0.001≤y≤0.05, or may be 0.002≤y≤0.04.

[0042] The Mg concentration of the interior 1 and the surface portion 2 of the positive electrode active material particle 5 according to the present embodiment can be checked, for example, by transmission electron microscopy (TEM)-energy dispersive X-ray spectroscopy (EDX). More specifically, the measurement object is first prepared in the following manner: the positive electrode active material particle 5 is embedded in an appropriate resin and subjected to cross-section polishing machine processing, etc., so that the cross section of the positive electrode active material particle 5 is exposed. Then, the cross section is inspected by TEM at an appropriate magnification. In the TEM inspection image thus obtained, the center of gravity and the outermost surface of the positive electrode active material particle 5 are analyzed by EDX to determine the concentration (mol %) of Mg atoms in each part. It is also preferred to perform EDX line analysis along a straight line extending from a point on the outermost surface of the positive electrode active material particle 5 to the center of gravity. The line analysis enables accurate tracking of the change in the concentration of Mg atoms from the surface to the center of gravity of the positive electrode active material particle 5.

[0043] The Mg concentration in the inner portion 1 of the positive electrode active material particle 5 may be 0.5 mol % to 8.0 mol %, preferably 1.0 mol % to 6.0 mol %, or 2.0 mol % to 5.0 mol %. The Mg concentration in the surface portion 2 of the positive electrode active material particle 5 may be 0.5 mol % or less, preferably 0.1 mol % to 5.0 mol %, or 0.2 mol % to 4.0 mol %.

[0044] The difference between the Mg concentration of the interior 1 of the positive electrode active material particle 5 and the Mg concentration of the surface portion 2 of the positive electrode active material particle 5 is preferably 1.0 mol% or more. When the difference satisfies the above range, both the suppression of the initial resistance increase and the suppression of the capacity retention rate degradation can be achieved. More preferably, the difference between the Mg concentration of the interior 1 of the positive electrode active material particle 5 and the Mg concentration of the surface portion 2 of the positive electrode active material particle 5 may be 2.0 mol% or more, or 2.5 mol% or more, or 3.0 mol% or more. It should be noted that from the perspective of the manufacture of the positive electrode active material particle 5, it may be, for example, 5.0 mol% or less.

[0045] The crystallite diameter of the positive electrode active material particle 5 can be 450Å to 900Å. Here, crystallite refers to a region (block) that can be regarded as a single crystal in the crystal structure of a single positive electrode active material particle 5, and the crystallite diameter refers to the size of the crystallite. As the crystallite diameter, a value calculated from an X-ray diffraction (XRD) line profile by the Scherrer formula can be used. As the crystallite diameter of the positive electrode active material particle 5 according to the present embodiment, the crystallite diameter based on the (003) plane that appears as a main peak in the X-ray diffraction line profile can be used. For example, the crystallite diameter of the positive electrode active material particle 5 can be obtained by calculating the half-value width of the (003) plane observed in the range of 2θ=19.1 to 20.1 of the spectrum obtained by XRD measurement by the Scherrer formula.

[0046] Typically, the positive electrode active material particles 5 are secondary particles formed by primary particles aggregated together. For example, the average particle size (D50) of the positive electrode active material particles 5 may be 4.0 μm to 8.0 μm, or D50 may be 5.0 μm to 7.0 μm. Here, D50 refers to the particle size at which the cumulative frequency accumulated from the small particle size side in the volume-based particle size distribution reaches 50%. D50 can be measured by laser diffraction.

[0047] The shape of the positive electrode active material particle 5 is not particularly limited; for example, it can be approximately spherical, flaky, columnar, etc., and is preferably approximately spherical. "Approximately spherical" is a term covering spheres, rugby balls, polygons, etc., and for example, it refers to a shape with an average aspect ratio (i.e., the ratio of the major axis length to the minor axis length of the smallest circumscribed rectangle of the particle) of 1 to 2.

[0048] The positive electrode active material particles 5 may include, for example, transition metal oxides, polyanion compounds, and the like.

[0049] <Transition metal oxides: space group R-3m>

[0050] The transition metal oxide may have any crystal structure. For example, the transition metal oxide may include a crystal structure belonging to space group R-3m, etc. For example, the general formula "LiMO 2 The compound represented by " may have a crystal structure belonging to the space group R-3m. The transition metal oxide may be represented, for example, by the following formula (A-1).

[0051] Li 1-a Ni x M 1-x O 2 (A-1)

[0052] In the above formula, the relationship of -0.5≤a≤0.5 and 0≤x≤1 is satisfied.

[0053] M may include, for example, at least one selected from the group consisting of Co, Mn, and Al.

[0054] In the above formula (A-1), x may satisfy, for example, the relationship of 0 < x ≤ 0.1, 0.1 ≤ x ≤ 0.2, 0.2 ≤ x ≤ 0.3, 0.3 ≤ x ≤ 0.4, 0.4 ≤ x ≤ 0.5, 0.5 ≤ x ≤ 0.6, 0.6 ≤ x ≤ 0.7, 0.7 ≤ x ≤ 0.8, 0.8 ≤ x ≤ 0.9, or 0.9 ≤ x ≤ 1. a may satisfy, for example, the relationship of -0.4 ≤ a ≤ 0.4, -0.3 ≤ a ≤ 0.3, -0.2 ≤ a ≤ 0.2, or -0.1 ≤ a ≤ 0.1.

[0055] The transition metal oxide may include, for example, at least one selected from the group consisting of LiCoO 2 , LiMnO 2 , LiNi 0.9 Co 0.1 O 2 , LiNi 0.9 Mn 0.1 O 2 and LiNiO 2 组成的组的至少一种。

[0056] <ncm>

[0057] The transition metal oxide can be represented, for example, by the following formula (A-2). The compound represented by the following formula (A-2) may also be referred to as "NCM".

[0058] Li 1-a Ni x Co y Mn z O 2 (A-2)

[0059] In the above formula, the relationships of -0.5 ≤ a ≤ 0.5, 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1 are satisfied.

[0060] In the above formula (A-2), x can satisfy, for example, the relationships of 0 < x ≤ 0.1, 0.1 ≤ x ≤ 0.2, 0.2 ≤ x ≤ 0.3, 0.3 ≤ x ≤ 0.4, 0.4 ≤ x ≤ 0.5, 0.5 ≤ x ≤ 0.6, 0.6 ≤ x ≤ 0.7, 0.7 ≤ x ≤ 0.8, 0.8 ≤ x ≤ 0.9, or 0.9 ≤ x < 1.

[0061] In the above formula (A-2), y can satisfy, for example, the relationships of 0 < y ≤ 0.1, 0.1 ≤ y ≤ 0.2, 0.2 ≤ y ≤ 0.3, 0.3 ≤ y ≤ 0.4, 0.4 ≤ y ≤ 0.5, 0.5 ≤ y ≤ 0.6, 0.6 ≤ y ≤ 0.7, 0.7 ≤ y ≤ 0.8, 0.8 ≤ y ≤ 0.9, or 0.9 ≤ y < 1.

[0062] In the above formula (A-2), z can satisfy, for example, the relationships of 0 < z ≤ 0.1, 0.1 ≤ z ≤ 0.2, 0.2 ≤ z ≤ 0.3, 0.3 ≤ z ≤ 0.4, 0.4 ≤ z ≤ 0.5, 0.5 ≤ z ≤ 0.6, 0.6 ≤ z ≤ 0.7, 0.7 ≤ z ≤ 0.8, 0.8 ≤ z ≤ 0.9, or 0.9 ≤ z < 1.

[0063] NCM may contain, for example, those selected from the group consisting of LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiNi 0.4 Co 0.3 Mn 0.3 O 2 、LiNi 0.3 Co 0.4 Mn 0.3 O 2 、LiNi 0.3 Co 0.3 Mn 0.4 O 2 、LiNi 0.5 Co 0.2 Mn 0.3 O 2 、LiNi 0.5 Co 0.3 Mn 0.2 O 2 、LiNi 0.5 Co 0.4 Mn 0.1 O 2 、LiNi 0.5 Co 0.1 Mn 0.4 O 2 、LiNi 0.6 Co 0.2 Mn 0.2 O 2 、LiNi 0.6 Co 0.3 Mn 0.1 O 2 、LiNi 0.6 Co 0.1 Mn 0.3 O 2 、LiNi 0.7 Co 0.1 Mn 0.2 O 2 、LiNi 0.7 Co 0.2 Mn 0.1 O 2 、LiNi 0.8 Co 0.1 Mn 0.1 O 2 and LiNi 0.9 Co 0.05 Mn 0.05 O 2 At least one of the groups consisting of.

[0064] <nca>

[0065] The transition metal oxide can be represented, for example, by the following formula (A-3). The compound represented by the following formula (A-3) may also be referred to as "NCA".

[0066] Li 1-a Ni x Co y Al z O 2 (A-3)

[0067] In the above formula, the relationships of -0.5 ≤ a ≤ 0.5, 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1 are satisfied.

[0068] In the above formula (A-3), x can satisfy, for example, the relationships of 0 < x ≤ 0.1, 0.1 ≤ x ≤ 0.2, 0.2 ≤ x ≤ 0.3, 0.3 ≤ x ≤ 0.4, 0.4 ≤ x ≤ 0.5, 0.5 ≤ x ≤ 0.6, 0.6 ≤ x ≤ 0.7, 0.7 ≤ x ≤ 0.8, 0.8 ≤ x ≤ 0.9, or 0.9 ≤ x < 1.

[0069] In the above formula (A-3), y can satisfy, for example, the relationships of 0 < y ≤ 0.1, 0.1 ≤ y ≤ 0.2, 0.2 ≤ y ≤ 0.3, 0.3 ≤ y ≤ 0.4, 0.4 ≤ y ≤ 0.5, 0.5 ≤ y ≤ 0.6, 0.6 ≤ y ≤ 0.7, 0.7 ≤ y ≤ 0.8, 0.8 ≤ y ≤ 0.9, or 0.9 ≤ y < 1.

[0070] In the above formula (A-3), z can satisfy, for example, the relationships of 0 < z ≤ 0.1, 0.1 ≤ z ≤ 0.2, 0.2 ≤ z ≤ 0.3, 0.3 ≤ z ≤ 0.4, 0.4 ≤ z ≤ 0.5, 0.5 ≤ z ≤ 0.6, 0.6 ≤ z ≤ 0.7, 0.7 ≤ z ≤ 0.8, 0.8 ≤ z ≤ 0.9, or 0.9 ≤ z < 1.

[0071] NCA may contain, for example, those selected from the group consisting of LiNi 0.7 Co 0.1 Al 0.2 O 2 、LiNi 0.7 Co 0.2 Al 0.1 O 2 、LiNi 0.8 Co 0.1 Al 0.1 O 2 、LiNi 0.8 Co 0.17 Al 0.03 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 and LiNi 0.9 Co 0.05 Al 0.05 O 2 At least one of the groups consisting of.

[0072] <Multi-component system>

[0073] The positive electrode active material particles 5 may include, for example, two or more NCMs. The positive electrode active material particles 5 may include, for example, NCM (0.6≤x) and NCM (x<0.6). "NCM (0.6≤x)" refers to a compound in which x (Ni ratio) is 0.6 or more in the above formula (A-2). NCM (0.6≤x) may also be referred to as, for example, "high nickel material". NCM (0.6≤x) includes, for example, LiNi 0.8 Co 0.1 Mn 0.1 O 2 etc. "NCM (x<0.6)" refers to compounds in the above formula (A-2) where x (Ni ratio) is less than 0.6. NCM (x<0.6) includes, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 The mixing ratio (mass ratio) between NCM (0.6≤x) and NCM (x<0.6) can be, for example, "NCM (0.6≤x) / NCM (x<0.6)=9 / 1 to 1 / 9", or "NCM (0.6≤x) / NCM (x<0.6)=9 / 1 to 4 / 6", or "NCM (0.6≤x) / NCM (x<0.6)=9 / 1 to 3 / 7".

[0074] The positive electrode active material particles 5 may include, for example, NCA and NCM. The mixing ratio (mass ratio) between NCA and NCM may be, for example, "NCA / NCM=9 / 1 to 1 / 9", "NCA / NCM=9 / 1 to 4 / 6", or "NCA / NCM=9 / 1 to 3 / 7". The Ni ratios of NCA and NCM may be the same, or may be different. The Ni ratio of NCA may be greater than the Ni ratio of NCM. The Ni ratio of NCA may be less than the Ni ratio of NCM.

[0075] <Transition metal oxides: space group C2 / m>

[0076] The transition metal oxide may include, for example, a crystal structure belonging to space group C2 / m, etc. The transition metal oxide may be represented, for example, by the following formula (A-4).

[0077] Li 2 MO 3 (A-4)

[0078] In the above formula, M may include, for example, at least one selected from the group consisting of Ni, Co, Mn, and Fe.

[0079] The positive electrode active material particles 5 may include, for example, LiMO 2 (space group R-3m) and Li 2 MO 3 (space group C2 / m). The positive electrode active material particles 5 may include, for example, LiMO 2 and Li 2 MO 3 The solid solution (Li 2 MO 3 -LiMO 2 )wait.

[0080] <Transition Metal Oxides: Space Group Fd-3m>

[0081] The transition metal oxide may include, for example, a crystal structure belonging to the space group Fd-3m, etc. The transition metal oxide may be represented, for example, by the following formula (A-5).

[0082] LiMn 2-x M x O 4 (A-5)

[0083] In the above formula, the relationship of 0≤x≤2 is satisfied.

[0084] M may include, for example, at least one selected from the group consisting of Ni, Fe, and Zn.

[0085] LiM 2 O 4 (space group Fd-3m) may include, for example, selected from LiMn 2 O 4 and LiMn 1.5 Ni 0.5 O 4 The positive electrode active material particles 5 may include, for example, LiMO 2 (space group R-3m) and LiM 2 O 4 (space group Fd-3m). For example, LiMO 2 (space group R-3m) and LiM 2 O 4 The mixing ratio (mass ratio) between (space group Fd-3m) can be, for example, "LiMO 2 / LiM 2 O 4 =9 / 1 to 9 / 1", or "LiMO 2 / LiM 2 O 4 =9 / 1 to 5 / 5" or "LiMO 2 / LiM 2 O 4 =9 / 1 to 7 / 3”.

[0086] <Polyanionic compounds>

[0087] The polyanionic compound may include, for example, phosphates (e.g., LiFePO 4 ), silicate, borate, etc. The polyanion compound can be represented by the following formulae (A-6) to (A-9), for example.

[0088] LiMPO 4 (A-6)

[0089] Li 2-x MPO 4 F (A-7)

[0090] Li 2 MSiO 4 (A-8)

[0091] LiMBO 3 (A-9)

[0092] In the above formulae (A-6) to (A-9), M may contain, for example, at least one selected from the group consisting of Fe, Mn, and Co. In the above formula (A-7), for example, the relationship of 0≤x≤2 is satisfied.

[0093] The positive electrode active material particles 5 may include, for example, LiMO 2 A mixture of (space group R-3m) and polyanionic compounds. LiMO 2 The mixing ratio (mass ratio) between the (space group R-3m) and the polyanionic compound may be, for example, "LiMO 2 / (polyanionic compound)=9 / 1 to 9 / 1", or "LiMO 2 / (polyanionic compound) = 9 / 1 to 5 / 5" or "LiMO 2 / (polyanionic compound)=9 / 1 to 7 / 3".

[0094] <Dopant>

[0095] A dopant may be added to the positive electrode active material particles 5. The dopant may be diffused throughout the particle, or may be locally distributed. For example, the dopant may be locally distributed on the particle surface. The dopant may be a substitutional solid solution atom, or may be an interstitial solid solution atom. The amount of the dopant added (relative to the molar fraction of the total amount of the positive electrode active material particles 5) may be, for example, 0.01% to 5%, or may be 0.1% to 3%, or may be 0.1% to 1%. A single type of dopant may be added, or two or more types of dopants may be added. Two or more dopants may form a composite.

[0096] The dopant may include, for example, at least one selected from the group consisting of B, C, N, halogen, Si, Na, Mg, Al, Mn, Co, Cr, Sc, Ti, V, Cu, Zn, Ga, Ge, Se, Sr, Y, Zr, Nb, Mo, In, Pb, Bi, Sb, Sn, W, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and actinides.

[0097] For example, a combination of "Zr, Mg, W, Sm", a combination of "Ti, Mn, Nb, Si, Mo", or a combination of "Er, Mg" may be added to NCA.

[0098] For example, Ti may be added to NCM. For example, a combination of "Zr, W", a combination of "Si, W", or a combination of "Zr, W, Al, Ti, Co" may be added to NCM.

[0099] <Surface coating>

[0100] The positive electrode may include composite particles. The composite particles include core particles and a covering layer. The core particles include positive electrode active material particles 5. The covering layer covers at least a portion of the surface of the core particles. The thickness of the covering layer may be, for example, 1 to 3000 nm, or 5 to 2000 nm, or 10 to 1000 nm, or 10 to 100 nm, or 10 to 50 nm. The thickness of the covering layer may be measured, for example, in an SEM (scanning electron microscope) image of a cross section of the particle. More specifically, the composite particles are embedded in a resin material to prepare a sample. An ion milling instrument is used to expose the cross section of the sample. For example, an ion milling instrument (or similar product) with a trade name of "ArBlade (registered trademark) 5000" manufactured by Hitachi High-Technologies Corporation may be used. The cross section of the sample is examined by SEM. For example, a SEM instrument (or similar product) with a trade name of "SU8030" manufactured by Hitachi High-Technologies Corporation may be used. For ten composite particles, the thickness of the covering layer is measured in twenty fields of view, respectively. The arithmetic mean of a total of 200 thickness measurements is used.

[0101] The ratio of the portion of the surface of the core particle covered by the covering layer is also referred to as "coverage". The coverage may be, for example, 1% or more, 10% or more, 30% or more, 50% or more, or 70% or more. The coverage may be, for example, 100% or less, 90% or less, or 80% or less.

[0102] For example, the coverage can be measured by XPS (X-ray photoelectron spectroscopy). For example, an XPS instrument (or similar product) manufactured by ULVAC-PHI under the trade name "PHI X-tool" can be used. The sample powder composed of the composite particles is loaded in the XPS instrument. A narrow scan analysis is performed. The measurement data is processed with analysis software. For example, analysis software (or similar product) manufactured by ULVAC-PHI under the trade name "MulTiPak" can be used. The measurement data is analyzed to detect multiple types of elements. The ratio of the detected elements is determined by the area of ​​each peak. The coverage is determined by the following formula.

[0103] θ={I 1 / (I 0 +I 1 )}×100

[0104] θ: Coverage [%]

[0105] I 0 : The ratio of the elements belonging to the core particle

[0106] I 1 : The ratio of elements belonging to the covering layer

[0107] For example, when the core particle comprises NCM, 0 represents the total ratio of the elements "Ni, Co, Mn". For example, when the core particle comprises NCA, I 0 represents the total ratio of the elements "Ni, Co, Al". For example, when the covering layer contains P and B, I 1 Indicates the total ratio of elements "P, B".

[0108] The covering layer may include any component. The covering layer may include, for example, a simple substance, an organic substance, an inorganic acid salt, an organic acid salt, a hydroxide, an oxide, a carbide, a nitride, a sulfide, a halide, etc. The covering layer may include, for example, at least one selected from the group consisting of B, Al, W, Zr, Ti, Co, F, a lithium compound (e.g., Li 2 CO 3 、LiHCO 3 、LiOH、Li 2 O), tungsten oxides (such as WO 3 ), titanium oxides (such as TiO 2 ), zirconium oxides (such as ZrO 2 ), boron oxides, borophosphates (such as BPO 4 ), aluminum oxides (such as Al 2 O 3 ), boehmite, aluminum hydroxide, phosphates [such as Li 3 PO 4 NH 4 ) 3 PO 4 、AlPO 4 ], borates (such as Li 2 B 4 O 7 、LiBO 3 ), polyacrylates (e.g. Li salts, Na salts, NH 4 salts), acetates (e.g., Li salts), CMC (e.g., acidic, Na salts, Li salts, NH 4 Salt), LiNbO 3 , Li 2 TiO 3 and Li-containing halides (e.g. LiAlCl 4 、LiTiAlF 6 ,LiYBr 6 、LiYCl 6 ).

[0109] <Hollow particles, solid particles>

[0110] "Hollow particles" refer to secondary particles in which the area ratio of the central cavity in the cross-sectional image is more than 30% of the entire cross-sectional area of ​​the particle. The proportion of the cavity in the hollow particle can be, for example, more than 40%, or more than 50% or more than 60%. "Solid particles" refer to secondary particles in which the area ratio of the central cavity in the cross-sectional image of the particle is less than 30% of the entire cross-sectional area of ​​the particle. The proportion of the cavity in the solid particle can be, for example, less than 20%, or less than 10% or less than 5%. The positive electrode active material particles 5 can be hollow particles, or can be solid particles. A mixture of hollow particles and solid particles can be used. For example, the mixing ratio (mass ratio) between the hollow particles and the solid particles can be, for example, "(hollow particles) / (solid particles)=1 / 9 to 9 / 1", or "(hollow particles) / (solid particles)=2 / 8 to 8 / 2", or "(hollow particles) / (solid particles)=3 / 7 to 7 / 3", or "(hollow particles) / (solid particles)=4 / 6 to 6 / 4".

[0111] <Large Particles / Small Particles>

[0112] "Electrode active material" is a general term for positive electrode active materials and negative electrode active materials. The electrode active material may have, for example, a unimodal particle size distribution (based on number). The electrode active material may have, for example, a multimodal particle size distribution. The electrode active material may have, for example, a bimodal particle size distribution. That is, the electrode active material may contain large particles and small particles. When the particle size distribution is bimodal, the particle size corresponding to the peak of the larger particle size is regarded as the particle size of the large particle (d L The particle size corresponding to the peak of the smaller particle size is regarded as the particle size of the small particle (d S ). Particle size ratio (d L / d S ) can be, for example, 2 to 10, or 2 to 5, or 2 to 4. L It may be, for example, 8 to 20 μm or 8 to 15 μm. S It may be, for example, 1 to 10 μm or 1 to 5 μm.

[0113] For example, using waveform analysis software, you can perform peak separation on the particle size distribution. For example, the peak area (S L ) and the peak area of ​​small particles (S S ) can be "S L / S S =1 / 9 to 9 / 1”, or "S L / S S =5 / 5 to 9 / 1” or "S L / S S =7 / 3 to 9 / 1”.

[0114] The particle size distribution based on quantity is measured by microscopy. Multiple cross-sectional samples are taken from the electrode active material layer. The cross-sectional samples may include, for example, cross-sections perpendicular to the surface of the electrode active material layer. The surface to be observed is cleaned by, for example, ion milling. The cross-sectional samples are inspected by SEM. The magnification of the inspection is adjusted in such a way that 10 to 100 particles are contained in the inspection field. The Feret diameter of all particles in the image is measured. "Feret diameter" refers to the distance between the two points on the contour line of the secondary particle that are farthest from each other. The multiple cross-sectional samples are inspected to obtain a total of more than 1000 Feret diameters. A particle size distribution based on quantity is created from the more than 1000 Feret diameters.

[0115] Bimodal particle size distribution can be formed by mixing two types of particles. These two types of particles have particle size distributions that are different from each other. For example, these two types of particles can have D50s that are different from each other. "D50" refers to the particle size at which the cumulative frequency accumulated from the small particle size side in the particle size distribution of the volume basis reaches 50%. D50 can be measured by laser diffraction. The sample to be measured is a powder. For example, the D50 of the large particle can be 8 to 20 μm or 8 to 15 μm. For example, the D50 of the small particle can be 1 to 10 μm or 1 to 5 μm. The ratio of the D50 of the large particle to the D50 of the small particle can be, for example, 2 to 10, or 2 to 5, or 2 to 4. The mixing ratio (mass ratio) between the large particle and the small particle can be, for example, "(large particle) / (small particle)=1 / 9 to 9 / 1", or "(large particle) / (small particle)=5 / 5 to 9 / 1", or "(large particle) / (small particle)=7 / 3 to 9 / 1".

[0116] The large particle and the small particle may have the same composition, or may have different compositions. For example, the large particle may be NCA, and the small particle may be NCM. For example, the large particle may be NCM (0.6≤x), and the small particle may be NCM (x<0.6).

[0117] <<Method for producing positive electrode active material particles>>

[0118] As a method of producing positive electrode active material particles according to the present embodiment, for example, the following method can be mentioned. The following description is given as an example and does not limit the scope of the production method.

[0119] The method of producing positive electrode active material particles according to the present embodiment includes, for example, “(A) preparation of a precursor” and “(B) calcination”.

[0120] <(A) Preparation of precursor>

[0121] The present manufacturing method includes preparing a precursor of positive electrode active material particles. The method for preparing the precursor is not particularly limited. For example, a mixed hydroxide of Mg and a transition metal (such as Ni) is prepared. For example, the powder of the mixed hydroxide is crushed in a mortar. For example, the crushed powder of the mixed hydroxide is dissolved in an alkaline aqueous solution to form a mixed solution. For example, the alkaline aqueous solution may include an aqueous NaOH solution, an ammonia solution, etc. For example, an acidic aqueous solution and an alkaline aqueous solution are simultaneously added dropwise to the mixed solution to form a precipitate. During the dropping process, the pH can be adjusted. It is believed that the precipitate contains a composite hydroxide (precursor). The precipitate is washed and dried to form a dried product.

[0122] Alternatively, a sulfate of Mg and a transition metal (e.g., Ni) is prepared. The sulfate is dissolved in water to form an acidic aqueous solution. For example, an alkaline aqueous solution is added dropwise to the acidic aqueous solution so that a neutralization reaction can occur. For example, the alkaline aqueous solution can include an aqueous NaOH solution, aqueous ammonia, etc. Through the neutralization reaction, a precipitate can be formed. During the neutralization reaction, the pH can be adjusted. It is believed that the precipitate contains a precursor. The precipitate is cleaned and dried to form a dried product.

[0123] <(B) Calcination>

[0124] The dried product thus obtained is mixed with a lithium compound to form a mixture. For example, the lithium compound may include Li 2 CO 3 , LiOH, etc. The mixture is heat treated (calcined). The calcination temperature may be, for example, 500 to 1000° C. The calcination duration may be, for example, 5 to 30 hours. In this way, positive electrode active material particles are manufactured.

[0125] <<Lithium-ion battery>>

[0126] Figure 2 1 is a conceptual diagram showing an example of a lithium ion battery according to the present embodiment. The battery 100 includes a power generation element 50 and an electrolyte (not shown).

[0127] <Outer Packaging>

[0128] The battery 100 may include an outer package (not shown). The outer package may contain a power generation element 50 and an electrolyte. The outer package may have any form. For example, the outer package may be a shell made of metal, or may be a bag made of a metal foil laminate film. The shell may be of any shape. For example, the shell may be cylindrical, square, flat, coin-shaped, etc. The outer package may contain, for example, Al, etc. The outer package may, for example, contain a single power generation element 50, or may contain a plurality of power generation elements 50. The plurality of power generation elements 50 may, for example, form a series circuit, or may form a parallel circuit. Inside the outer package, the plurality of power generation elements 50 may be stacked in the thickness direction of the battery 100.

[0129] <Power Generation Element>

[0130] The power generation element 50 may also be referred to as an "electrode group", "electrode assembly", etc. The power generation element 50 includes a positive electrode 10 and a negative electrode 20. The power generation element 50 may also include a separator 30. The separator 30 is inserted between the positive electrode 10 and the negative electrode 20. The power generation element 50 may have any form. For example, the power generation element 50 may be a stacked power generation element. For example, the positive electrode 10 and the negative electrode 20 may be alternately stacked with the separator 30 inserted between the positive electrode 10 and the positive electrode 20 to form the power generation element 50. For example, the power generation element 50 may be a wound power generation element. For example, a positive electrode 10 having a strip shape, a separator 30 having a strip shape, and a negative electrode 20 having a strip shape may be stacked to form a stack. The resulting stack may be wound into a spiral shape to form the power generation element 50. After winding, the wound power generation element 50 may be formed into a flat form.

[0131] <Positive electrode>

[0132] The positive electrode 10 may be in the form of a sheet, for example. The positive electrode 10 includes a positive electrode collector 11 and a positive electrode active material layer 12. The positive electrode collector 11 has conductivity. The positive electrode collector 11 supports the positive electrode active material layer 12. The positive electrode collector 11 may be in the form of a sheet, for example. The thickness of the positive electrode collector 11 may be, for example, 5 to 50 μm. The positive electrode collector 11 may include, for example, a metal foil. The positive electrode collector 11 may include, for example, at least one selected from the group consisting of Al, Mn, Ti, Fe, and Cr. The positive electrode collector 11 may include, for example, Al foil, Al alloy foil, Ti foil, stainless steel (SUS) foil, etc.

[0133] An intermediate layer (not shown) may be formed between the positive electrode current collector 11 and the positive electrode active material layer 12. The intermediate layer does not contain positive electrode active material particles. The thickness of the intermediate layer may be, for example, 0.1 to 5 μm. The intermediate layer may contain, for example, a conductive material, an insulating material, an adhesive, etc. The conductive material and the adhesive are described below. The insulating material may include, for example, aluminum oxide, boehmite, aluminum hydroxide, etc.

[0134] The positive electrode active material layer 12 is placed on the surface of the positive electrode collector 11. The positive electrode active material layer 12 may be placed only on one side of the positive electrode collector 11. The positive electrode active material layer 12 may be placed on both sides of the positive electrode collector 11. For example, the positive electrode active material layer 12 may have a thickness of 10 μm or more, or may have a thickness of 50 μm or more, or may have a thickness of 80 μm or more, or may have a thickness of 100 μm or more. It is believed that when the positive electrode active material layer 12 is thick, more specifically, when its thickness is 80 μm or more, the durability retention rate is even more improved. The positive electrode active material layer 12 may have a thickness of 1000 μm or less, or may have a thickness of 500 μm or less, or may have a thickness of 300 μm or less. The positive electrode active material layer 12 contains positive electrode active material particles. The positive electrode active material layer 12 may also contain, for example, a conductive material, a binder, carbon nanotubes, etc.

[0135] <<Conductive Materials>>

[0136] The conductive material may form an electron conduction path inside the positive electrode active material layer 12. The amount of the conductive material used may be, for example, 0.1 to 10 parts by mass relative to 100 parts by mass of the positive electrode active material particles. The conductive material may include any component. The conductive material may include, for example, at least one selected from the group consisting of graphite, acetylene black (AB), Ketjen black (registered trademark), vapor grown carbon fiber (VGCF), carbon nanotube (CNT) and graphene sheet (GF).

[0137] <<Adhesive>>

[0138] The binder can fix the positive electrode active material layer 12 to the positive electrode current collector 11. The amount of the binder used can be, for example, 0.1 to 10 parts by mass relative to 100 parts by mass of the positive electrode active material particles. The binder can include any component. The binder can include, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), tetrafluoroethylene (PTFE), CMC, PAA, polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyoxyethylene alkyl ether and derivatives of these substances.

[0139] <<Carbon Nanotubes>>

[0140] The electron conductivity of carbon nanotubes (CNT) is high. Therefore, when the positive electrode active material layer 12 includes CNT, the electron conductivity is ensured, and as a result, the initial resistance and capacity retention rate are expected to improve. In addition, CNT is preferably contained in the interior of the positive electrode active material particles. When CNT is contained in the interior of the positive electrode active material particles, it is expected that the CNT forms a composite, which can more reliably ensure the electron conductivity.

[0141] The aspect ratio of the CNT may be, for example, 20 or more. When the aspect ratio of the CNT is 20 or more, the CNT tends to be contained in the interior 1 of the positive electrode active material particle 5, so that resistance reduction is expected. The aspect ratio of the CNT may be 100 or more.

[0142] The aspect ratio is the ratio of length to diameter. Here, "aspect ratio" is determined by dividing the average length of the CNT by the average diameter of the CNT. The average length and the average diameter can each be the arithmetic mean of the measured values ​​of more than ten CNTs. The length and diameter of a single CNT are measured using a TEM or scanning electron microscope (SEM).

[0143] The average diameter of the CNT may be, for example, 10 nm to 50 nm. The average length of the CNT may be, for example, 1 μm to 5 μm.

[0144] The content of the CNT in the positive electrode active material layer 12 may be, for example, 0.1% to 5.0% by mass. When the content of the CNT in the positive electrode active material layer 12 satisfies the above range, initial resistance and capacity retention are expected to improve. Preferably, the content of the CNT in the positive electrode active material layer 12 is 0.5% to 4.0% by mass.

[0145] <<Other ingredients>>

[0146] The positive electrode active material layer 12 may further include, for example, inorganic fillers, organic fillers, solid electrolytes, surface modifiers, lubricants, flame retardants, protective agents, fluxes, coupling agents, adsorbents, etc. The positive electrode active material layer 12 may include, for example, polyoxyethylene allylphenyl ether phosphate / ester, zeolite, silane coupling agent, MoS 2 , WO 3 wait.

[0147] <Negative electrode>

[0148] The negative electrode 20 may be in the form of a sheet, for example. The negative electrode 20 may include, for example, a negative electrode current collector 21 and a negative electrode active material layer 22. The negative electrode current collector 21 has conductivity. The negative electrode current collector 21 supports the negative electrode active material layer 22. The negative electrode current collector 21 may be in the form of a sheet, for example. The thickness of the negative electrode current collector 21 may be, for example, 5 to 50 μm. The negative electrode current collector 21 may include, for example, a metal foil, etc. The negative electrode current collector 21 may include, for example, at least one selected from the group consisting of Cu, Ni, Fe, Zn, Pb, Ag, and Au. The negative electrode current collector 21 may include, for example, Cu foil, Cu alloy foil, etc.

[0149] The negative electrode active material layer 22 is placed on the surface of the negative electrode collector 21. The negative electrode active material layer 22 may be placed only on one side of the negative electrode collector 21. The negative electrode active material layer 22 may be placed on both sides of the negative electrode collector 21. The thickness of the negative electrode active material layer 22 may be, for example, 10 to 1000 μm, or 50 to 500 μm, or 100 to 300 μm. The negative electrode active material layer 22 contains a negative electrode active material. The negative electrode active material layer may also contain, for example, a conductive material, a binder, and the like.

[0150] The thickness of the negative electrode active material layer 22 may be, for example, 10 to 1000 μm, or 50 to 500 μm, or 100 to 300 μm. The negative electrode active material layer 22 contains a negative electrode active material. The negative electrode active material layer may further contain, for example, a conductive material, a binder, and the like.

[0151] <<Conductive Materials>>

[0152] The conductive material may form an electron conduction path inside the negative electrode active material layer 22. The content of the conductive material may be, for example, 0.1 to 10 parts by mass relative to 100 parts by mass of the negative electrode active material. The conductive material may include any component. For example, the conductive material may include at least one selected from the group consisting of graphite, AB, Ketjen black, VGCF, CNT and GF. The CNT may include at least one selected from the group consisting of single-walled CNT (SWCNT) and multi-walled CNT (MWCNT).

[0153] <<Adhesive>>

[0154] The binder can fix the negative electrode active material layer 22 to the negative electrode current collector 21. The content of the binder can be, for example, 0.1 to 10 parts by mass relative to 100 parts by mass of the negative electrode active material. The binder can include any component. The binder can include, for example, at least one selected from the group consisting of styrene-butadiene rubber (SBR), acrylic butadiene rubber (ABR), sodium alginate, carboxymethyl cellulose (e.g., CMC-H, CMC-Na, CMC-Li, CMC-NH 4 ), polyacrylic acid (e.g. PAA-H, PAA-Na, PAA-Li), polyacrylonitrile (PAN), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), acrylic resin (acrylate copolymer), methacrylic resin (methacrylate copolymer), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), and derivatives thereof. For example, the expression "CMC-Na" refers to the Na salt of CMC. For example, the expression "CMC-H" refers to acid-type CMC. The same applies to "PAA-Na" and the like.

[0155] <<Other ingredients>>

[0156] The negative electrode active material layer 22 may further include, for example, inorganic fillers, organic fillers, solid electrolytes, surface modifiers, dispersants, lubricants, flame retardants, protective agents, fluxes, coupling agents, adsorbents, etc. The negative electrode active material layer may include, for example, layered silicates (e.g., smectite, montmorillonite, bentonite, hectorite), inorganic fillers (e.g., solid alumina, hollow silica, boehmite), polysiloxane compounds, etc.

[0157] <<Negative Electrode Active Materials>>

[0158] The negative electrode active material may include, for example, a material selected from the group consisting of natural graphite, artificial graphite, soft carbon, hard carbon, silicon (Si), SiO, Li silicate, silicon-based alloys, tin (Sn), SnO, Sn-based alloys, and Li 4 Ti 5 O 12 At least one of the groups consisting of.

[0159] <Carbon-based active materials>

[0160] The "graphite" is a general term for natural graphite and artificial graphite. The graphite may be a mixture of natural graphite and artificial graphite. The mixing ratio (mass ratio) may be, for example, "(natural graphite) / (artificial graphite)=1 / 9 to 9 / 1", or "(natural graphite) / (artificial graphite)=2 / 8 to 8 / 2", or "(natural graphite) / (artificial graphite)=3 / 7 to 7 / 3".

[0161] The graphite may contain a dopant. The dopant may contain, for example, at least one selected from the group consisting of B, N, P, Li, and Ca. In terms of molar fraction, the addition amount may be, for example, 0.01% to 5%, or 0.1% to 3%, or 0.1% to 1%.

[0162] The surface of the graphite may be covered with, for example, amorphous carbon. The surface of the graphite may be covered with, for example, other types of materials. The other types of materials may include, for example, at least one selected from the group consisting of P, W, Al, and O. The other types of materials may include, for example, at least one selected from the group consisting of Al(OH) 3 , AlOOH, Al 2 O 3 , WO 3 , Li 2 CO 3 , LiHCO 3 , and Li 3 PO 4 consisting of the group.

[0163] <Alloy-based active material>

[0164] SiO can be represented, for example, by the following formula (B-1).

[0165] SiO x (B-1)

[0166] In the above formula, the relationship 0 < x < 2 is satisfied.

[0167] In the above formula (B-1), x may satisfy, for example, 0.5 ≤ x ≤ 1.5 or 0.8 ≤ x ≤ 1.2.

[0168] Li silicate may include, for example, at least one selected from the group consisting of Li 4 SiO 4 , Li 2 SiO 3 , Li 2 Si 2 O 5 , and Li 8 SiO 6 consisting of the group. The second negative electrode active material may include, for example, a mixture of Si and Li silicate. The mixing ratio (mass ratio) may be, for example, "Si / (Li silicate) = 1 / 9 to 9 / 1", or "Si / (Li silicate) = 2 / 8 to 8 / 2", or "Si / (Li silicate) = 3 / 7 to 7 / 3", or "Si / (Li silicate) = 4 / 6 to 6 / 4".

[0169] The alloy-based active material (e.g., Si, SiO) may contain additives. The additives may be, for example, substitutional solid solution atoms or interstitial solid solution atoms. The additives may be attachments adhered to the surface of the alloy-based active material. The attachments may be, for example, simple substances, oxides, carbides, nitrides, halides, etc. In terms of mole fraction, the addition amount may be, for example, 0.01% to 5%, or 0.1% to 3% or 0.1% to 1%. The additives may contain, for example, at least one selected from the group consisting of Li, Na, K, Rb, Be, Mg, Ca, Sr, Fe, Ba, B, Al, Ga, In, C, Ge, Sn, Pb, N, P, As, Y, Sb, and S. That is, SiO may be doped with Mg and / or Na. For example, Mg silicate and / or Na silicate may be formed. For example, boron oxide (e.g., B 2 O 3 ), yttrium oxide (e.g., Y 2 O 3 ) etc. may be added to SiO.

[0170] <Si-C Composite Material>

[0171] The negative electrode active material may contain, for example, a composite material of the carbon-based active material (e.g., graphite) and the alloy-based active material (e.g., Si). The composite material containing Si and carbon may also be referred to as "Si-C composite material". For example, Si fine particles may be dispersed inside carbon particles. For example, Si fine particles may be dispersed inside graphite particles. For example, Li silicate particles may be covered with a carbon material (e.g., amorphous carbon). The Si-C composite material and graphite may be used by mixing them together.

[0172] <Multi-Component System>

[0173] The negative electrode active material may contain two or more components. The negative electrode active material may contain the carbon-based active material (e.g., graphite) and the alloy-based active material (e.g., Si, SiO). The mixing ratio (mass ratio) of the carbon-based active material and the alloy-based active material may be, for example, "(carbon-based active material) / (alloy-based active material)=1 / 9 to 9 / 1", or "(carbon-based active material) / (alloy-based active material)=2 / 8 to 8 / 2", or "(carbon-based active material) / (alloy-based active material)=3 / 7 to 7 / 3" or "(carbon-based active material) / (alloy-based active material)=4 / 6 to 6 / 4".

[0174] <Separator>

[0175] The separator 30 can separate the positive electrode 10 from the negative electrode 20. The separator 30 is electrically insulating. The separator 30 may include, for example, at least one selected from the group consisting of a resin film, an inorganic particle layer, and an organic particle layer. The separator 30 may include, for example, a resin film and an inorganic particle layer.

[0176] <<Resin Film>>

[0177] The resin film is porous. The resin film may include, for example, a microporous film, a nonwoven fabric, etc. The resin film includes a resin skeleton. The resin skeleton may be, for example, in a continuous mesh form. The gaps in the resin skeleton form pores. The resin film allows electrolyte to penetrate therethrough. The average pore size of the resin film may be, for example, less than 1 μm. The average pore size of the resin film may be, for example, 0.01 to 1 μm or 0.1 to 0.5 μm. The "average pore size" may be measured by mercury porosimetry. The Gurley value of the resin film may be, for example, 50 to 250 s / 100cm 3 The "Gurley value" can be measured by the Gurley test method.

[0178] The resin film may include, for example, at least one selected from the group consisting of olefin resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, acrylic resins, polyester resins, etc. The resin film may include, for example, at least one selected from the group consisting of polyethylene (PE), polypropylene (PP), polyamide (PA), polyamide-imide (PAI), polyimide (PI), aromatic polyamide (aramid) and polyphenylene ether (PPE) and derivatives thereof. The resin film may be formed by, for example, stretching, phase separation, etc. The thickness of the resin film may be, for example, 5 to 50 μm or 10 to 25 μm.

[0179] The resin film may have a single-layer structure. The resin film may, for example, be composed of a PE layer. The skeleton of the PE layer is formed of PE. The PE layer may have a closed-cell function. The resin film may have, for example, a multilayer structure. The resin film may include, for example, a PP layer and a PE layer. The skeleton of the PP layer is formed of PP. The resin film may have, for example, a three-layer structure. The resin film may, for example, be formed by stacking a PP layer, a PE layer, and a PP layer in sequence. The thickness of the PE layer may be, for example, 5 to 20 μm. The thickness of the PP layer may be, for example, 3 to 10 μm.

[0180] <<Inorganic particle layer>>

[0181] The inorganic particle layer may be formed on the surface of the resin film. The inorganic particle layer may be formed only on one side of the resin film, or may be formed on both sides of the resin film. The inorganic particle layer may be formed on the surface facing the positive electrode 10, or may be formed on the surface facing the negative electrode 20. The inorganic particle layer may be formed on the surface of the positive electrode 10, or may be formed on the surface of the negative electrode 20.

[0182] The inorganic particle layer is porous. The inorganic particle layer contains inorganic particles. The inorganic particles may also be referred to as "inorganic fillers". The gaps between the inorganic particles form pores. The thickness of the inorganic particle layer may be, for example, 0.5 to 10 μm or 1 to 5 μm. The inorganic particles may contain, for example, heat-resistant materials. The inorganic particle layer containing heat-resistant materials is also referred to as "HRL (heat-resistant layer)". The inorganic particles may contain at least one selected from the group consisting of boehmite, alumina, zirconium oxide, titanium dioxide, magnesium oxide, silicon dioxide, etc. The inorganic particles may be in any shape. The inorganic particles may be, for example, spherical, rod-shaped, plate-shaped, fibrous, etc. The D50 of the inorganic particles may be, for example, 0.1 to 10 μm or 0.5 to 3 μm. The inorganic particle layer may also contain an adhesive. The adhesive may contain, for example, at least one selected from the group consisting of acrylic resins, polyamide resins, fluorine resins, aromatic polyether resins, and liquid crystal polyester resins.

[0183] <<Organic particle layer>>

[0184] The diaphragm 30 may include, for example, an organic particle layer. The diaphragm 30 may include, for example, an organic particle layer instead of the resin film. The diaphragm 30 may include, for example, an organic particle layer instead of the inorganic particle layer. The diaphragm 30 may include both the resin film and the organic particle layer. The diaphragm 30 may include both the inorganic particle layer and the organic particle layer. The diaphragm 30 may include the resin film, the inorganic particle layer, and the organic particle layer.

[0185] The thickness of the organic particle layer may be, for example, 0.1 to 50 μm, or 0.5 to 20 μm, or 0.5 to 10 μm, or 1 to 5 μm. The organic particle layer contains organic particles. The organic particles may also be referred to as "organic fillers". The organic particles may contain heat-resistant materials. The organic particles may contain, for example, at least one selected from the group consisting of PE, PP, PTFE, PI, PAI, PA, aramid, etc. The organic particles may be, for example, spherical, rod-shaped, plate-shaped, fibrous, etc. The D50 of the organic particles may be, for example, 0.1 to 10 μm or 0.5 to 3 μm.

[0186] The separator 30 may include, for example, a mixed layer including both inorganic particles and organic particles.

[0187] <Electrolytes>

[0188] The electrolyte dissolves Li ions therein. The electrolyte may be a liquid electrolyte, or may be a gel electrolyte. The liquid electrolyte may include, for example, an electrolyte solution. The electrolyte solution includes a solvent and a solute.

[0189] <<Solvents>>

[0190] <Ether solvent>

[0191] The electrolyte may include, for example, an ether solvent, etc. The solvent may include, for example, a hydrofluoroether (HFE), etc. The HFE may include, for example, at least one selected from the group consisting of a difluoromethyl group, a 2,2-difluoroethyl group, a 2,2,2-trifluoroethyl group, a 1,1,2,2-tetrafluoroethyl group, a 2,2,3,3,3-pentafluoropropyl group, a 2,2,3,3-tetrafluoropropyl group, a 1,1,1,3,3,3-hexafluoroisopropyl group, a 1,1,2,3,3,3-hexafluoropropyl group, a 2,2,3,3,4,4,4-heptafluorobutyl group, a 2,2,3,3,4,4-hexafluorobutyl group, and a 2,2,3,3,4,4,5,5-octafluoropentyl group.

[0192] The solvent may further include an ether other than HFE (the ether may also be referred to as "second ether" hereinafter). The second ether may include, for example, at least one selected from the group consisting of tetrahydrofuran (THF), 1,4-dioxane (DOX), 1,3-dioxolane (DOL), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), ethyl glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and derivatives thereof. For example, the solvent may include 1% to 50% by volume of the second ether (e.g., DME), and the rest is composed of HFE. For example, the solvent may include 10% to 40% by volume of the second ether, and the rest is composed of HFE.

[0193] <Carbonate-based solvents>

[0194] The electrolyte may include, for example, a carbonate-based solvent (a carbonate-based solvent). The solvent may include, for example, a cyclic carbonate, a chain carbonate, a fluorinated carbonate, etc. The solvent may include, for example, at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (FEC), difluoroethylene carbonate, 4,4-difluoroethylene carbonate, trifluoroethylene carbonate, perfluoroethylene carbonate, fluoropropylene carbonate, difluoropropylene carbonate, and derivatives of these substances.

[0195] The solvent may include cyclic carbonate (e.g., EC, PC, FEC) and linear carbonate (e.g., EMC, DMC, DEC). The mixing ratio (volume ratio) between the cyclic carbonate and the linear carbonate may be, for example, "(cyclic carbonate) / (linear carbonate)=1 / 9 to 4 / 6", or "(cyclic carbonate) / (linear carbonate)=2 / 8 to 3 / 7", or "(cyclic carbonate) / (linear carbonate)=3 / 7 to 4 / 6".

[0196] The solvent may include cyclic carbonate (e.g., EC, PC) and fluorinated cyclic carbonate (e.g., FEC). The mixing ratio (volume ratio) between the cyclic carbonate and the fluorinated cyclic carbonate may be, for example, "(cyclic carbonate) / (fluorinated cyclic carbonate)=99 / 1 to 90 / 10", or "(cyclic carbonate) / (fluorinated cyclic carbonate)=9 / 1 to 1 / 9", or "(cyclic carbonate) / (fluorinated cyclic carbonate)=9 / 1 to 7 / 3", or "(cyclic carbonate) / (fluorinated cyclic carbonate)=3 / 7 to 1 / 9".

[0197] The solvent may include, for example, EC, FEC, EMC, DMC, and DEC. The volume ratio of these components may satisfy, for example, the relationship represented by the following formula (C-1).

[0198] V EC +V FEC +V EMC +V DMC +V DEC =10 (C-1)

[0199] In the above formula, V EC 、V FEC 、V EMC 、V DMC and V DEC Represent the volume ratios of EC, FEC, EMC, DMC and DEC respectively.

[0200] Satisfies the following relationship: 1≤V EC ≤4, 0≤V FEC ≤3, V EC +V FEC ≤4, 0≤V EMC ≤9, 0≤V DMC ≤9, 0≤V DEC ≤9, 6≤V EMC +V DMC +V DEC ≤9.

[0201] In the above formula (C-1),

[0202] For example, 1≤V EC ≤2 or 2≤V EC The relationship is ≤3.

[0203] For example, 1≤V FEC ≤2 or 2≤V FEC The relationship is ≤4.

[0204] For example, 3≤V EMC ≤4 or 6≤V EMC The relationship is ≤8.

[0205] For example, 3≤V DMC ≤4 or 6≤V DMC The relationship is ≤8.

[0206] For example, 3≤V DEC ≤4 or 6≤V DEC The relationship is ≤8.

[0207] The composition of the solvent can be, for example, "EC / EMC=3 / 7", "EC / DMC=3 / 7", "EC / FEC / DEC=1 / 2 / 7", "EC / DMC / EMC=3 / 4 / 3", "EC / DMC / EMC=3 / 3 / 4", "EC / FEC / DMC / EMC=2 / 1 / 4 / 3", "EC / FEC / DMC / EMC=1 / 2 / 4 / 3", "EC / FEC / DMC / EMC=2 / 1 / 3 / 4", "EC / FEC / DMC / EMC=1 / 2 / 3 / 4" (volume ratio), etc.

[0208] <Additives>

[0209] The electrolyte may contain any additives. The addition amount (mass fraction of the total amount of the electrolyte) may be, for example, 0.01% to 5%, or 0.05% to 3%, or 0.1% to 1%. The additives may include, for example, SEI (solid electrolyte interface) formation promoters, SEI formation inhibitors, gas generators, overcharge inhibitors, flame retardants, antioxidants, electrode protective agents, surfactants, etc.

[0210] The additive may include, for example, at least one selected from the group consisting of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), 1,3-propane sultone (PS), tert-amylbenzene, 1,4-di-tert-butylbenzene, biphenyl (BP), cyclohexylbenzene (CHB), ethylene sulfite (ES), propane sultone, ethylene sulfate (DTD), γ-butyrolactone, phosphazene compounds, carboxylic acid esters [e.g., methyl formate (MF), acetic acid methyl ester (MA), methyl propionate (MP), diethyl malonate (DEM)], fluorobenzenes (e.g., monofluorobenzene (FB), 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,3,5-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, 1,2,3,5-tetrafluorobenzene, 1,2,4,5-tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene), fluorotoluenes (e.g., 2-fluorotoluene, 3 4-Fluorotoluene, 2-fluorotoluene, 3-fluorotoluene, 4-fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,6-difluorotoluene, 3,4-difluorotoluene, octafluorotoluene), trifluorotoluenes (e.g. trifluorotoluene, 2-fluorotoluene, 3-fluorotoluene, 4-fluorotoluene, 2-methyltoluene, 3-methyltoluene, 4-methyltoluene), fluoroxylenes (e.g. 3-fluoro-o-xylene, 4-fluoro-o-xylene, 2-fluoro-m-xylene, benzene, 5-fluoro-m-xylene), sulfur-containing heterocyclic compounds (such as benzothiazole, 2-methylbenzothiazole, tetrathiafulvalene), nitrile compounds (such as adiponitrile, succinonitrile), phosphates / esters (such as trimethyl phosphate, triethyl phosphate), carboxylic anhydrides (such as acetic anhydride, propionic anhydride, oxalic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, benzoic anhydride), alcohols (such as methanol, ethanol, n-propanol, ethylene glycol, diethylene glycol monomethyl ether) and derivatives of these substances.

[0211] The above-mentioned components as solute and solvent may be used as trace components (additives). The additive may include, for example, a compound selected from the group consisting of LiBF 4 , LiFSI, LiTFSI, LiBOB, LiDFOB, LiDFOP, LiPO 2 F 2 、FSO 3 At least one of the group consisting of Li, LiI, LiBr, HFE, DOX, PC, FEC and derivatives thereof.

[0212] <<Ionic Liquids>>

[0213] The liquid electrolyte may include an ionic liquid. The liquid electrolyte may include, for example, at least one selected from the group consisting of sulfonium salts, ammonium salts, pyridinium salts, piperidinium salts, pyrrolidinium salts, morpholinium salts, phosphonium salts, imidazolium salts, and derivatives thereof.

[0214] <<Gel Electrolyte>>

[0215] The gel electrolyte may include a liquid electrolyte and a polymer material. The polymer material may form a polymer matrix. The polymer material may include, for example, at least one selected from the group consisting of PVdF, PVdF-HFP, PAN, PVdF-PAN, polyethylene oxide (PEO), polyethylene glycol (PEG) and derivatives of these substances.

[0216] <Battery composition>

[0217] Figure 3 : is a table showing the first battery configuration. Figure 4 : is a table showing the second battery configuration. Figure 5 is a table showing a third battery configuration. In each table, when a plurality of materials are described in one cell, the description is intended to mean one of them and a combination thereof. For example, when materials "α, β, γ" are described in one cell, the description is intended to mean "at least one selected from the group consisting of α, β, and γ". Specific elements can be extracted from the first to third battery configurations and arbitrarily combined together.

[0218] For example, the present embodiment can be incorporated into the first to third battery configurations. The positive electrode in the first battery configuration can be replaced by the positive electrode (positive electrode current collector 11, positive electrode active material layer 12) according to the present embodiment. For example, combining the first to third battery configurations with the present embodiment can improve battery performance.

[0219] [Example]

[0220] Hereinafter, the present embodiment will be described using examples, but the present embodiment is not limited to these examples. Hereinafter, the method for manufacturing the positive electrode active material particles No. 2 to 4 may be referred to as a "doping method", the method for manufacturing the positive electrode active material particles No. 5 to 7 may be referred to as a "MHP method", and the method for manufacturing the positive electrode active material particles No. 8 to 10 may be referred to as a "post-addition method".

[0221] <Manufacturing of positive electrode active material particles>

[0222] (No. 1)

[0223] An aqueous solution of nickel sulfate (1.8 mol / L) is prepared (hereinafter, "mol / L" may also be simply expressed as "M"). An aqueous solution of NaOH (1.0 M) is added dropwise to the aqueous solution of nickel sulfate to form a precipitate. The addition of the aqueous solution of NaOH is adjusted so that the pH is maintained at 11.6. The precipitate is washed and dried to form a dry product. The dry product is mixed with LiOH to form a mixture. The mixture thus formed has a mixing ratio (Li / Ni) (molar ratio) of Li and Ni of 1.04. The mixture is calcined. The calcination temperature is 880°C. The calcination time is 6 hours. In this way, positive electrode active material particles No. 1 having a layered rock salt structure are synthesized. It was also checked that the positive electrode active material particles Nos. 2 to 10 described below also have a layered rock salt structure.

[0224] (No. 2)

[0225] Nickel sulfate and magnesium sulfate were dissolved in water to prepare an acidic aqueous solution (1.8 M). The blending ratio (molar ratio) of the solutes was (nickel sulfate): (magnesium sulfate) = 96.8:3.2. An aqueous NaOH solution (1.0 M) was added dropwise to the acidic aqueous solution to form a precipitate. The addition of the NaOH aqueous solution was adjusted so that the pH was maintained at 11.6. The precipitate was washed and dried to form a dry product. The dry product was mixed with LiOH to form a mixture. The mixture thus formed had a mixing ratio (Li / (Ni+Mg)) (molar ratio) of Li to Ni and Mg of 1.04. The calcination temperature was 880°C. The calcination time was 6 hours. In this way, the positive electrode active material particles No. 2 were synthesized.

[0226] (No. 3 to 4)

[0227] The positive electrode active material particles of No. 3 and No. 4 were synthesized under the same conditions as those of No. 2, but for No. 3, the blending ratio of the solute in the acidic aqueous solution was changed to (nickel sulfate): (magnesium sulfate) = 94.4:5.6, and for No. 4, the blending ratio of the solute in the acidic aqueous solution was changed to (nickel sulfate): (magnesium sulfate) = 98.7:1.3.

[0228] (No. 5)

[0229] A mixed hydroxide of nickel hydroxide and magnesium hydroxide was prepared. The blending ratio (molar ratio) was (nickel hydroxide): (magnesium hydroxide) = 96.7:3.1. The powder of the mixed hydroxide was crushed in a mortar until D50 reached about 3 μm. The crushed powder of the mixed hydroxide was dissolved in ammonia water (mass concentration, 10%) to prepare a mixed solution. An aqueous solution of nickel sulfate (1.8 M) and an aqueous solution of NaOH (1.0 M) were simultaneously added dropwise to the resulting mixed solution to form a precipitate. The addition of the aqueous solution of nickel sulfate and the aqueous solution of NaOH was adjusted so that the pH was maintained at 11.6. The precipitate was washed and dried to form a dried product. The dried product was mixed with LiOH to form a mixture. The mixture thus formed had a mixing ratio (Li / (Ni+Mg)) (molar ratio) of Li to Ni and Mg of 1.04. The calcination temperature was 880°C. The calcination time was 6 hours. In this way, the positive electrode active material particles No. 5 were synthesized.

[0230] (No. 6 to 7)

[0231] The positive electrode active material particles of No. 6 and No. 7 were synthesized under the same conditions as those of No. 5, but for No. 6, the blending ratio of the mixed hydroxide was (nickel hydroxide): (magnesium hydroxide) = 94.2:5.8, and for No. 7, the blending ratio of the solute in the mixed hydroxide was (nickel hydroxide): (magnesium hydroxide) = 99.1:0.9.

[0232] (No. 8)

[0233] Prepare the positive electrode active material particles of No. 1. Mix the positive electrode active material particles with magnesium oxide to form a mixture. The mixing ratio (Ni:Mg) (molar ratio) of Ni and Mg of the mixture thus formed is 96.9:3.1. Calcinate the mixture. The calcination temperature is 500° C. The calcination time is 5 hours. In this way, the positive electrode active material particles of No. 8 are synthesized.

[0234] (No. 9 to 10)

[0235] The positive electrode active material particles of Nos. 9 and 10 were synthesized under the same conditions as those of No. 8, but for No. 9, the mixing ratio of Ni and Mg was 94.6:5.4, and for No. 10, the mixing ratio of Ni and Mg was 98.9:1.1.

[0236] <Manufacturing of lithium-ion batteries>

[0237] (Example 1)

[0238] The positive electrode of Example 1 was produced using the following materials.

[0239] <<Positive Electrode>>

[0240] Positive electrode active material particles: No. 2

[0241] Conductive material: AB (Denka)

[0242] Adhesive: PVDF (Kureha)

[0243] Furthermore, a test cell for evaluation of Example 1 was produced using the following materials.

[0244] <<Negative Electrode>>

[0245] Negative electrode active material: Natural graphite (Hitachi Chemical Co., Ltd.)

[0246] Adhesive: CMC (Nippon Paper Industries), SBR (JSR Corporation)

[0247] <<Others>>

[0248] Diaphragm: porous sheet (thickness 24 μm)

[0249] Electrolyte: electrolyte [LiPF 6 (1 M), EC+DMC+EMC]

[0250] (Example 2)

[0251] The positive electrode and the test cell for evaluation of Example 2 were manufactured under the same conditions as those of Example 1, except that the positive electrode active material particles of Example 2 were No. 3.

[0252] (Examples 3 to 5)

[0253] The positive electrodes of Examples 3 to 5 and the test cells for evaluation were manufactured under the same conditions as those of Example 1, except that 0.4 mass % of CNTs were added to the positive electrode of Example 1, 1.0 mass % of CNTs were added to the positive electrode of Example 1, and 4.0 mass % of CNTs were added to the positive electrode of Example 1, respectively.

[0254] (Examples 6 to 8)

[0255] The positive electrodes and test cells for evaluation of Examples 6 to 8 were manufactured under the same conditions as those of Example 1, except that the positive electrode active material particles of Example 6 were No. 5, the positive electrode active material particles of Example 7 were No. 6, and the positive electrode active material particles of Example 8 were No. 7.

[0256] (Examples 9 to 11)

[0257] The positive electrodes and evaluation test cells of Examples 9 to 11 were manufactured under the same conditions as those of Example 1, except that 0.4 mass % CNTs were added to the positive electrode of Example 6, 1.0 mass % CNTs were added to the positive electrode of Example 6, and 4.0 mass % CNTs were added to the positive electrode of Example 6, respectively.

[0258] (Comparative Example 1)

[0259] The positive electrode and the test cell for evaluation of Comparative Example 1 were manufactured under the same conditions as those of Example 1, except that the positive electrode active material particles of Comparative Example 1 were No. 1.

[0260] (Comparative Example 2)

[0261] The positive electrode and the test cell for evaluation of Comparative Example 2 were manufactured under the same conditions as those of Example 1, except that the positive electrode active material particles of Comparative Example 2 were No. 4.

[0262] (Comparative Examples 3 to 5)

[0263] The positive electrodes and evaluation test cells of Comparative Examples 3 to 5 were manufactured under the same conditions as those of Example 1, except that the positive electrode active material particles of Comparative Example 3 were No. 8, the positive electrode active material particles of Comparative Example 4 were No. 9, and the positive electrode active material particles of Comparative Example 5 were No. 10.

[0264] (Comparative Examples 6 to 8)

[0265] The positive electrodes of Comparative Examples 6 to 8 and the test cells for evaluation were manufactured under the same conditions as those of Example 1, except that 0.4 mass % CNTs were added to the positive electrode of Comparative Example 3, 1.0 mass % CNTs were added to the positive electrode of Comparative Example 3, and 4.0 mass % CNTs were added to the positive electrode of Comparative Example 3, respectively.

[0266] <Analysis>

[0267] <<Composition>>

[0268] ICP-AES was performed to examine the compositions of the interior and surface of the positive electrode active material particles Nos. 1 to 10. As the composition of the interior of the positive electrode active material particle, the composition at the center of gravity of the positive electrode active material particle was examined, and as the composition of the surface of the positive electrode active material particle, the composition of the outermost surface of the positive electrode active material particle was examined. The composition of each positive electrode active material particle was Figure 6 Shown in.

[0269] <<Magnesium Concentration>>

[0270] TEM-EDX as described above was performed to examine the Mg concentration (mol %) inside and on the surface of the positive electrode active material particles No. 1 to 10. As the Mg concentration inside the positive electrode active material particles, the Mg concentration at the center of gravity of the positive electrode active material particles was examined, and as the Mg concentration on the surface of the positive electrode active material particles, the Mg concentration on the outermost surface of the positive electrode active material particles was examined. The Mg concentration inside and on the surface of each positive electrode active material particle was 1.3477 W / m2. Figure 6 In Figure 6 In the figure, the difference between the Mg concentration inside the positive electrode active material particle and the Mg concentration on the surface of the positive electrode active material particle (internal concentration)-(surface concentration) is expressed as "Mg concentration difference".

[0271] <Evaluation>

[0272] (Initial resistance)

[0273] Each test cell was charged to 3.6 V and then discharged at a current value of 10 C for 10 seconds in a room temperature environment, and the voltage at a time point 10 seconds after the start of discharge was measured; the IV resistance (resistance) was calculated from the result to determine the initial resistance. Figure 6 The results are shown as relative values ​​relative to the initial resistance (set to 100) of the test battery of Comparative Example 1. When the initial resistance was 150 or less, it was evaluated as good.

[0274] (Capacity retention rate)

[0275] After the initial resistance measurement, 100 charge and discharge cycles were performed at room temperature with a constant current of 1 C and a voltage in the range of 3.0 to 4.2 V. After the initial charge and discharge, the charge and discharge were performed at a current of 0.1 C and a voltage in the range of 3.0 to 4.2 V, and the discharge capacity at this time was defined as the initial discharge capacity; after the 100th charge and discharge, the charge and discharge were performed at a current of 0.1 C and a voltage in the range of 3.0 to 4.2 V, and the discharge capacity at this time was defined as the 100th discharge capacity. The 100th discharge capacity was divided by the initial discharge capacity to determine the capacity retention rate (in percentage). The results are Figure 6 A capacity retention rate of 75% or more was evaluated as good.

[0276] <Results>

[0277] (Initial resistance)

[0278] refer to Figure 6 In the example where the Mg concentration inside the positive electrode active material particles was higher than the Mg concentration on the surface of the positive electrode active material particles, the value of the initial resistance was good.

[0279] In addition, when comparison is made between Example 1 comprising positive electrode active material particles No. 2 manufactured by the doping method, Example 6 comprising positive electrode active material particles No. 5 manufactured by the MHP method, and Comparative Example 3 comprising positive electrode active material particles No. 8 manufactured by the post-addition method, the initial resistance of Example 6 manufactured by the MHP method is most suppressed, while the initial resistance in Comparative Example 3 manufactured by the post-addition method is the highest.

[0280] (Capacity retention rate)

[0281] refer to Figure 6 In the embodiment where the Mg concentration inside the positive electrode active material particles is higher than the Mg concentration on the surface of the positive electrode active material particles, a good capacity retention rate is maintained even after repeated charge and discharge.

[0282] In addition, when comparison is made between Example 1 comprising positive electrode active material particles No. 2 manufactured by the doping method, Example 6 comprising positive electrode active material particles No. 5 manufactured by the MHP method, and Comparative Example 3 comprising positive electrode active material particles No. 8 manufactured by the post-addition method, Example 6 manufactured by the MHP method has the highest capacity retention rate, while Comparative Example 3 manufactured by the post-addition method has the lowest capacity retention rate.

[0283] Furthermore, when Examples 9 to 11 including the positive electrode active material particles No. 5 produced by the MHP method and CNTs were compared with Example 6 including no CNTs, it was observed that the capacity retention ratio improved as the content rate of CNTs increased.

[0284] Furthermore, in Examples 6 to 11 including the cathode active material particles manufactured by the MHP method, the Mg concentration inside the cathode active material particles differed greatly from that on the surface, compared with Examples 1 to 5 including the cathode active material particles manufactured by the doping method.

[0285] Although the embodiments of the present disclosure have been described, the embodiments disclosed herein are illustrative and non-restrictive in any aspect. The scope of the present disclosure is defined by the terms of the claims, and is intended to encompass any modifications within the meaning and scope equivalent to the terms of the claims.< / nca> < / ncm>

Claims

1. A positive electrode active material particle, wherein The positive electrode active material particles have a layered rock salt type crystal structure, The positive electrode active material particles include a lithium composite oxide containing magnesium, and The magnesium concentration inside the positive electrode active material particle is higher than the magnesium concentration on the surface of the positive electrode active material particle.

2. The positive electrode active material particle according to claim 1, wherein The magnesium concentration in the interior is 0.5 mol % to 8.0 mol %, and The magnesium concentration in the surface portion is 5.0 mol % or less. 3 . The positive electrode active material particle according to claim 1 , wherein the difference between the magnesium concentration in the inner portion and the magnesium concentration in the surface portion is 1.0 mol % or more. 4 . A positive electrode comprising the positive electrode active material particles according to claim 1 . The positive electrode according to claim 4 , further comprising carbon nanotubes.

6. A lithium ion battery comprising the positive electrode according to claim 4 or 5.

Citation Information

Patent Citations

  • Cathode active material for nonaqueous electrolyte secondary battery, method for manufacturing the same, and nonaqueous electrolyte secondary battery

    JP2018088383A

  • Adhering method for protective sheet and processing method for wafer

    JP2023127491A